1985
DOI: 10.1080/05698198508981592
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Perfluoropolyalkylether Oil with FeF3, AlF3, and AlCl3at Elevated Temperatures

Abstract: The interaction of perfluoropolyalkylether (PFPE) oil with ferric pztoride (FeF3) and other Lewis acidr at elevated temperatures under inert atmosphere was investigated to determine whether the reaction results in lubricant degradation. At 35@C, -25°C below the onset of thermal degradation, PFPES reaction with FeF3 yields acyl fluoride and ketone degradation products and also a decrease in the oil's number-average molecular weight. In the presence of small quantities of water, the acyl halide products hydrolyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Broad bands in the 3600-3000, 1669, and 1436 cm 21 areas of Fig. 7 correlate well with other literature studies of polymeric fluorinated carboxylic acids (Carré and Markowitz 1985;Eapen et al 1994;Xuan et al 1993). The presence of a strong broad band at 3600-3000 cm 21 suggests that some of the adsorbed carboxylate is hydrogen-bonded.…”
Section: Postmortem Analysis Of Space Lubricants-fundamental Investigsupporting
confidence: 77%
See 2 more Smart Citations
“…Broad bands in the 3600-3000, 1669, and 1436 cm 21 areas of Fig. 7 correlate well with other literature studies of polymeric fluorinated carboxylic acids (Carré and Markowitz 1985;Eapen et al 1994;Xuan et al 1993). The presence of a strong broad band at 3600-3000 cm 21 suggests that some of the adsorbed carboxylate is hydrogen-bonded.…”
Section: Postmortem Analysis Of Space Lubricants-fundamental Investigsupporting
confidence: 77%
“…The spectroscopic evidence led to the proposed degradation pathway for all PFPE involving defluorination, chain scission, and formation of carbonyl end groups as suggested in prior literature (Carré 1985;Eapen et al 1994;Xuan et al 1993). Carboxylic acid groups form quickly when carbonyl groups react with humidity in the air, and in turn react with surface metal ion species to form carboxylates.…”
Section: Postmortem Analysis Of Space Lubricants-fundamental Investigmentioning
confidence: 88%
See 1 more Smart Citation
“…The hydrolysis of iron fluorides yields iron hydroxides and iron oxides and hence results in the rusting of iron. Iron fluorides are one of the Lewis acids that catalyze the degradation of lubricants [29,32]. Therefore, a decrease in the tribochemical reaction of the TFSA anion appears to be instrumental in improving the tribological properties of RT-ILs.…”
Section: Lubrication Mechanismmentioning
confidence: 99%
“…Research has repeatedly shown that PFPE's degrade while in boundary-lubricated,sliding/rolling contacts (5)(6)(7)(8)(9)(10) and at elevated temperatures (11)(12)(13)(14) losing their desirable properties, including lubricity.Although few models have been proposed to explain the observed degradation, it has been shown that the rate of degradation, under static, elevated temperature conditions, is dependent upon the surface chemistry of the substrate and relative strength of the Lewis acid substrates. Kasai (11) has shown that the thermal catalytic degradation of a PFPE depends upon the strength of the Lewis acid substrate present, and has proposed a chemical degradation mechanism for each of the four commercial PFPE's.…”
Section: Introductionmentioning
confidence: 99%